Regulating Alternative Crowdfunding: Legal Challenges in Advancing Indonesian SMEs Amid Consumer Protection, Transparency, and Strict Platform Oversight—A Comparison with Austria - Alfiani, Yudha; Syaugi, Syaugi; Wahyudi, Rofiul (Universitas Negeri Semarang, 2024)
Alternative crowdfunding has emerged as a vital financing solution for Small and Medium Enterprises (SMEs) in Indonesia, offering funding opportunities beyond traditional financial institutions and fostering economic growth. However, the Indonesian government must address risks such as fraud, personal data misuse, and investor losses by ensuring strong legal protection and regulatory oversight. This study examines the legal framework for equity-based crowdfunding and SME empowerment in Indonesia, drawing comparative insights from Austria’s well-established regulations. The novelty of this research lies in its comparative approach, which highlights regulatory asymmetries affecting investor confidence and SME access to funding. The urgency is underscored by Indonesia’s rapidly expanding digital finance sector, where weak governance could undermine crowdfunding’s potential. This normative legal study employs a descriptive-analytic approach, integrating legislative and conceptual perspectives from both jurisdictions. Findings indicate that Austria enforces investment limits, stringent platform accountability, and robust law enforcement, ensuring market stability while supporting SMEs. Conversely, Indonesia should ease SME access to crowdfunding while implementing investment caps to mitigate investor risks. Moreover, Austria’s strong judicial oversight and auditing mechanisms serve as a model for Indonesia, which requires enhanced regulatory enforcement and institutional capacity. This study contributes to legal scholarship by proposing a balanced regulatory model that fosters SME participation while ensuring investor protection, transparency, and sustainable market growth. By adopting best practices from Austria and Europe, Indonesia can refine its crowdfunding regulations to drive economic development while maintaining a secure financial ecosystem.